Awareness Regarding Anesthesiology and Anesthesiologists Among General Population in Developing Country- A Cross Sectional Survey - Khyati Pandya; Kamla H Mehta; Kirti D Patel (National Journal of Community Medicine, 2016)
Background: Anaesthesiologists are playing decisive role in pa- tient management. Nowadays, they are involved in pain clinic and critical care also but the general public know little about them. So this study was undertaken to assess the perception of general population from poor socioeconomic area regarding the anaesthe- siology and role of anaesthesiologists.